Restoring Public Confidence: Perceptions of Community Police Officers. (September 2014) - Wooden, Kenneth; Rogers, Colin
Community policing has often been viewed by many as a panacea for solving community-based problems. In particular, following instances of riot or other public disorder, police agencies have instigated this type of approach with a view to regaining support from within communities and restoring public confidence whilst reducing acts of criminality. Inherent within this approach is a focus upon the involvement of community members and their perceptions in order for this approach to succeed. However, such approaches appear to ignore the perceptions of front-line police officers, who are generally considered to be homogenous in their views and attitudes. This article suggests that the success of such community policing initiatives is reliant upon their acceptance by street police, those who have most contact with the public. Utilising the example of the disorders witnessed at Macquarie Fields, Sydney, Australia, the problems associated with this lack of understanding are explored, and discussed with a view to providing insights for police managers and community leaders alike.